2021
DOI: 10.1021/acs.orglett.1c01953
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylic Acid Deoxyfluorination and One-Pot Amide Bond Formation Using Pentafluoropyridine (PFP)

Abstract: This work describes the application of pentafluoropyridine (PFP), a cheap commercially available reagent, in the deoxyfluorination of carboxylic acids to acyl fluorides. The acyl fluorides can be formed from a range of acids under mild conditions. We also demonstrate that PFP can be utilized in a one-pot amide bond formation via in situ generation of acyl fluorides. This one-pot deoxyfluorination amide bond-forming reaction gives ready access to amides in yields of ≤94%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 51 publications
0
29
0
Order By: Relevance
“…Very recently, Cobb et al utilized pentafluoropyridine (PFP) as a deoxyfluorinating agent to form acyl fluorides in situ from carboxylic acids, and then constructed a series of amides and esters in good to excellent yields via intermolecular nucleophilic substitution with amines or alcohols as nucleophiles (Scheme 52b). 100…”
Section: Scheme a Classical Nucleophilic Substitution Reaction Of Acy...mentioning
confidence: 99%
“…Very recently, Cobb et al utilized pentafluoropyridine (PFP) as a deoxyfluorinating agent to form acyl fluorides in situ from carboxylic acids, and then constructed a series of amides and esters in good to excellent yields via intermolecular nucleophilic substitution with amines or alcohols as nucleophiles (Scheme 52b). 100…”
Section: Scheme a Classical Nucleophilic Substitution Reaction Of Acy...mentioning
confidence: 99%
“…Perfluoropyridine has been employed as a nucleophilic fluorination reagent for both alkyl halides ( Scheme 6 , right-to-left ) [ 46 ] as well as deoxyfluorination of carboxylic acids ( Scheme 6 , left-to-right ) [ 47 ] for the preparation of a versatile pool of substrates. Fluorination of organo-halides (R–X) is achieved after generation of the air-stable fluoride salt from the addition of PFPy and dimethylaminopyridine [ 46 ].…”
Section: Chemistry Of Perfluoropyridinementioning
confidence: 99%
“…Fluorination of organo-halides (R–X) is achieved after generation of the air-stable fluoride salt from the addition of PFPy and dimethylaminopyridine [ 46 ]. Furthermore, the in situ generation of acyl fluorides is readily accomplished by the nucleophilic addition of carboxylic acids with PFPy [ 47 ]. The ester intermediate then undergoes cleavage from unsequestered fluoride, producing phenol as a by-product and the desired acyl fluoride.…”
Section: Chemistry Of Perfluoropyridinementioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, it was reported that pentafluoropyridine can also be employed to synthesise amide bonds. [21] By mixing a carboxylic acid with pentafluoropyridine it was shown that the corresponding acyl fluoride could be readily generated. By subsequent addition of an amine, the amide could be generated in good to excellent yield across a wide range of examples.…”
Section: Peptide Synthesismentioning
confidence: 99%